2011
DOI: 10.1016/j.jacc.2011.04.018
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Ability of Pre-Operative B-Type Natriuretic Peptide in Vascular Patients for Major Adverse Cardiac Events

Abstract: Pre-operative NP levels can be used to independently predict cardiovascular events in the first 30 days after vascular surgery and to significantly improve the predictive performance of the revised cardiac risk index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 39 publications
(53 reference statements)
4
77
0
5
Order By: Relevance
“…Presently, almost a quarter century after the first patients were entered in the model, use of the RCRI is now widespread. [8][9][10][11] In this interval, the diagnostic criteria for myocardial infarction have changed, 12 and we are unaware of any studies that have re-examined the two factors, diabetes and chronic renal failure. As a result, we submit there is a need to re-examine the accuracy and clinical utility of the index.…”
Section: Résumémentioning
confidence: 99%
“…Presently, almost a quarter century after the first patients were entered in the model, use of the RCRI is now widespread. [8][9][10][11] In this interval, the diagnostic criteria for myocardial infarction have changed, 12 and we are unaware of any studies that have re-examined the two factors, diabetes and chronic renal failure. As a result, we submit there is a need to re-examine the accuracy and clinical utility of the index.…”
Section: Résumémentioning
confidence: 99%
“…Хотя рутинное использо-вание КАГ показало свое преимущество в ряде прове-денных исследований [6,7,9,10], по-видимому, будут продолжены попытки разработать оптимальную батарею неинвазивных тестов, способных выявить больных с наиболее вероятным поражением коро-нарных артерий [13]. Это может быть оценка степени дилатации сердца при стресс-ЭхоКГ [8], оценка каль-циевого индекса, таких биомаркеров, как мозговой натрий-уретический пептид [14], С-реактинвый белок [15], проведение МСКТ-ангиографии коро-нарных артерий. При этом необходимо будет учиты-вать не только медицинские показания, но и эконо-мическую эффективность.…”
Section: Discussionunclassified
“…There are several meta-analyses and systematic reviews of studies evaluating BNPs in the surgical population; and they consistently demonstrate that BNPs, in particular when drawn preoperation compared with postoperation, are independent predictors of both short-and long-term adverse cardiac events, including cardiac deaths and all-cause mortality [143,144]. In addition, BNPs were found to be useful as a stratification tool to assess risk for postoperative cardiovascular complications [145]. A meta-analysis of vascular surgery patients found that increased preoperative BNP levels (including NT-proBNP) were associated with increased risk of 30-day postoperative cardiac events, cardiac-related mortality and all-cause deaths up to 180 days [144].…”
Section: Brain Natriuretic Peptides As a Marker Of Cardiovascular Rismentioning
confidence: 96%